Perencanaan Karier Mahasiswa Program Vokasi Perhotelan - Dewi Melati (Politeknik Sahid, 2020)
This research was conducted to see the career development plans of vocational education students majoring in hospitality management with a case study at the Jakarta International Polytechnic. The research results were available from a survey of 61 students. Career planning is very important for final semester students who will soon enter the world of work. The findings show that students majoring in hospitality management at the Jakarta International Polytechnic plan to develop a career in the hospitality industry according to the specialization they pursued during college, although there are some students who plan to have a career outside the specialization they choose. Countless students have long-term plans to become entrepreneurs after gaining experience.